2021
DOI: 10.1080/14427591.2021.1879239
|View full text |Cite
|
Sign up to set email alerts
|

A narrative analysis of the transition from driving to driving cessation in later life: Implications from an occupational lens

Abstract: The transition from driving to driving cessation in older adulthood is considered a major life transition where resulting disruptions can impact sense of self. Such transitions at this life stage offer both a challenge and opportunity to consider the relationship between disruption, adaptation (or not) of occupational patterns, and perceptions of life roles. The current study examines this process of adaptation where the focus is on exploring how disruption, loss, and identity over time are negotiated at this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…The equifinality in the participants’ trajectories had positive and negative consequences, but their positivity in developed countries was overwhelming (Sato & Tanimura, 2016). Our finding is consistent with Bertrand et al’s (2021) finding that individuals experienced progress, regress, and stabilization of occupational participation over time. However, occupational participation in low-resource settings is also characterized by exclusion, which indicates societal injustice.…”
Section: Discussionsupporting
confidence: 92%
“…The equifinality in the participants’ trajectories had positive and negative consequences, but their positivity in developed countries was overwhelming (Sato & Tanimura, 2016). Our finding is consistent with Bertrand et al’s (2021) finding that individuals experienced progress, regress, and stabilization of occupational participation over time. However, occupational participation in low-resource settings is also characterized by exclusion, which indicates societal injustice.…”
Section: Discussionsupporting
confidence: 92%
“…The aim of this study was to describe the experience of older persons and caregivers in the transition from driving to driving-cessation. Firstly, analysis of the results showed that driving occupied a central place in the lives of older persons, and was synonymous with freedom and independence, as other studies have already reported [14,15,28].…”
Section: Discussionmentioning
confidence: 88%
“…Similar results have been reported in other studies [14][15][16][17]30], where loss of freedom, independence, role, and occupation were also reported. The loss of a license is considered as one of the most difficult moments in older persons' lives [28]. In fact, it seems that older adults who gave more importance to drivingrelated identities had more difficulty adapting to alternative solutions, such as the use of public transportation, than those whose identity was not linked to the accessibility and autonomy offered by driving [10].…”
Section: Discussionmentioning
confidence: 99%